Global transcriptome analysis reveals potential genes associated with genic male sterility of rapeseed (Brassica napus L.) - Jiang, Jianxia; Xu, Pengfei; Zhang, Junying; Li, Yanli; Zhou, Xirong; Jiang, Meiyan; Zhu, Jifeng; Wang, Weirong; Yang, Liyong (Frontiers in Plant Science, 2022)
Rapeseed is the third leading source of edible oil in the world. Genic male sterility (GMS) lines provide crucial material for harnessing heterosis for rapeseed. GMS lines have been widely used successfully for rapeseed hybrid production. The physiological and molecular mechanism of pollen development in GMS lines of rapeseed (Brassica napus L.) need to be determined for the creation of hybrids and cultivation of new varieties. However, limited studies have focused on systematically mining genes that regulate the pollen development of GMS lines in B. napus. In the present study, to determine the stage at which pollen development begins to show abnormality in the GMS lines, we performed semi-thin section analysis of the anthers with five pollen development stages. The results indicated that the abnormal pollen development in DGMS lines might start at the meiotic stage, and abnormal pollen development in RGMS lines probably occurred before the tetrad stage. To investigate the critical genes and pathways involved in pollen development in GMS lines, we constructed and sequenced 24 transcriptome libraries for the flower buds from the fertile and sterile lines of two recessive GMS (RGMS) lines (6251AB and 6284AB) and two dominant GMS (DGMS) lines (4001AB and 4006AB). A total of 23,554 redundant DEGs with over two-fold change between sterile and fertile lines were obtained. A total of 346 DEGs were specifically related to DGMS, while 1,553 DEGs were specifically related to RGMS. A total of 1,545 DEGs were shared between DGMS and RGMS. And 253 transcription factors were found to be differentially expressed between the sterile and fertile lines of GMS. In addition, 6,099 DEGs possibly related to anther, pollen, and microspore development processes were identified. Many of these genes have been reported to be involved in anther and microspore developmental processes. Several DEGs were speculated to be key genes involved in the regulation of fertility. Three differentially expressed genes were randomly selected and their expression levels were verified by quantitative PCR (qRT-PCR). The results of qRT-PCR largely agreed with the transcriptome sequencing results. Our findings provide a global view of genes that are potentially involved in GMS occurrence. The expression profiles and function analysis of these DEGs were provided to expand our understanding of the complex molecular mechanism in pollen and sterility development in B. napus.